Hypocrisy in ethical consumption - Foad, Colin; Haddock, Geoff; Maio, Gregory (Frontiers in Psychology, 2022)
When making consumption choices, people often fail to meet their own standards of both ethics and frugality. People also generally tend to demand more of others than they do of themselves. But little is known about how these different types of hypocrisy interact, particularly in relation to attitudes toward ethical consumption. In three experiments, we integrate research methods using anchoring and hypocrisy within the context of ethical consumption. Across three experiments, we find a default expectation that people (particularly people other than ourselves) should spend less on consumer items than they actually do. This default position can be inverted by making the ethical context of consumption salient, whereby the expectation is then that people (particularly other people) should spend more on consumer items than they actually do. Experiments 2 and 3 show that a moderate price anchor for ethical consumption is sufficient to shift expected standards for other people, but a higher price anchor is required to shift expected standards in personal behaviour. We discuss the countervailing roles of frugality and ethical consumption in understanding hypocrisy and ethical decision-making.